Enhanced Blowfish Algorithm and EECC to Improve Cloud Storage Security - Srilekha, Thotakuri; Bhanu S., Vijay; P., Niranjan (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Several applications consist of huge volume of data associated to its function. Data handling is the major concern in all application which relies in internet, Cloud is feasible solution to store such data used in internet applications but the security is a big concern and its privacy, security parameters are also degraded when these data are placed in common private storage place. Generally numerous techniques of cryptography are being involved in securing those third party storage places but still it is integrity questionable. We have proposed a method named EBF-EECC (Enhanced Blowfish Algorithm –Enhanced Elliptic Curve Cryptography) for securing data as well as key. Key is encrypted separately by EECC and Data encrypted separately with the help of EBF. In addition with these techniques we deployed one more hash function along with EBF-EECC for concrete safety of the data pertaining to individual services in the cloud. Blowfish algorithm is still being used for securing the data in excellent manner with the help of Average size of the key, Number of rounds and the sizes of block and the same proved in our simulation. Elliptic curve cryptography is also considered in proposed method by taking their strong nature of key sizes considered with other algorithms like RSA to improve concrete security measurement on cloud data.